HIV/AIDS Prevention and Control Strategy for Transgender at the Yogyakarta Kebaya Foundation - Wahyuni, Tri; Prasetyo, Iis (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2022)
The general objective of the study is to describe the HIV/AIDS prevention and control strategy at the Kebaya Foundation. Specifically, this research aims to; (1) describe the strategy developed by the Kebaya Foundation in HIV/AIDS prevention and control, (2) describe the process of implementing HIV/AIDS prevention strategies at the Kebaya Foundation, (3) describe the Kebaya Foundation's efforts to improve the effectiveness of HIV/AIDS prevention and control strategies and (4) describe the results of the implementation of HIV/AIDS prevention and control strategies at the Kebaya Foundation.This study uses a descriptive qualitative approach which was conducted at the Yogyakarta Kebaya Foundation. Sources of research data are the Director of the Kebaya Foundation, Program Managers, and Volunteer Members. Other data sources are activities for implementing problem-solving strategies and efforts to improve the effectiveness of implementing strategies and activity documents at the Kebaya Foundation. Data collection techniques are interviews, observation, and documentation. The validity of the data through triangulation of sources and techniques. Credibility of the data using triangulation of sources and methods. Data analysis using Miles and Huberman's interactive analysis includes data collection, data reduction, data presentation, verification and drawing conclusions.The results of this study indicate; (1) The HIV/AIDS prevention and control strategy implemented by the Kebaya Foundation intensifies counseling and advocates for waria, outreach, community assistance, building social relations, budget advocacy, and improving transgender human resources. (2) The strategy implementation process is carried out through a series of stockist process activities, educational processes, and networked audience activities. (3) Efforts to increase the effectiveness of implementing the strategy are carried out by developing cooperation, intensifying education for transgender women, setting up Al-Falah waria boarding schools, routine VCT, counseling and mentoring. (4) The implementation of the strategy at the Kebaya Foundation has the impact of increasing ARV and VCT compliance, the implementation of shelters, and the emergence of support as a donor agency.